Vital village. Development of rural areas as a challenge for cultural policy. Entwicklung ländlicher Räume als kulturpolitische Herausforderung. - (:unkn) unknown (transcript, 2017)
Durch globale Transformationsprozesse und die gesellschaftlichen Herausforderungen des demographischen Wandels rücken ländliche Räume immer mehr in den Fokus von Politik und Öffentlichkeit. Die Beiträge zeigen für verschiedene europäische Länder, dass vor allem Kulturakteure relevante Anregungen für die zeitgemäße Gestaltung des sich verändernden Zusammenlebens geben. Insbesondere die Künste stellen dabei einen Nährboden für weiterführende Impulse dar. Das Buch führt Ergebnisse der Kulturpolitikforschung zusammen, stellt beispielhafte Modelle vor und wagt somit erstmals eine Positionsbestimmung innovativer Kulturarbeit in ländlichen Räumen.

Due to global processes of transformation and the social challenges posed by demographic change, rural areas increasingly demand attention from politics and the public sphere. The contributions in this volume demonstrate how in different European countries it is mainly the cultural players who offer suggestions for an organization of the changing forms of communal life that is keeping with the times. The arts in particular have proven to be able of providing fresh impetus and new insights. This compendium of theory and practice combines outcomes of studies in cultural policy, introduces exemplary models and thus constitutes a first attempt at determining the position of innovative cultural work in rural areas. All essays both in English and German.
Keywords: Regionalplanung; Regionalentwicklung; Ländlicher Raum; Kulturpolitik; Kunst; Kirche; Soziokultur; Zusammenleben; Demographischer Wandel; Digitalisierung